Role of porosity defects in metal 3D printing: Formation mechanisms, impacts on properties and mitigation strategies - Wang, Shuhao; Ning, Jinsheng; Zhu, Lida; Yang, Zhichao; Yan, Wentao; Dun, Yichao; Xue, Pengsheng; Xu, Peihua; Bose, Susmita; Bandyopadhyay, Amit (Materials today (Kidlington, England), 2022)
[Display omitted] Metal 3D printing (3DP), a state-of-the-art manufacturing technology that brings the potential to fabricate complex structures at low cost and reduced energy consumption, has been extensively adopted in various industries. However, the porosity defects inherited from the printing process can significantly impede the mechanical properties and weaken the performance of as-printed components, potentially challenging this approach's reliability and reproducibility. The advancement of detection techniques currently opens up a more intuitive and deeper study of porosity defects. Given that, this review systematically states the 'restriction role' of porosity defects in metal 3DP by generalizing the detailed information on porosity defects, including their characterizations, formation and migration mechanisms, and their impacts on the performance of printed parts. Furthermore, feasible porosity mitigation measures are discussed to inspire more advanced methodologies for the next generation of metal 3DP.